Notes on the Cambridge translation of Kant’s Religion within the Boundaries of Mere Reason - DiCenso, James (Con-Textos Kantianos. International Journal of Philosophy, 2023)
This article mainly discusses translation issues in the two Cambridge editions of Kant’s Religion, while engaging in a briefer discussion of Pluhar’s translation of the same work. The aim is to correct single errors as well as patterns of questionable translation, and to do so guided by criteria of consistency in relation to Kant’s use of key terms. I argue that the English translations have contributed to misinterpretations of Kant’s philosophy of religion, although I make only passing references to the secondary scholarship.